(untitled) (Eurasian Journal of Media and Communications, 2025)
This article explores the emerging role of nanoimplants in facial bone regeneration, highlighting recent advancements in nanotechnology and their applications in craniofacial reconstructive surgery. It reviews current literature, discusses methodologies for integrating nanoimplants, and evaluates their efficacy in promoting bone regeneration. The article also examines challenges, future directions, and potential clinical implications, emphasizing the balance between bioactivity, therapeutic efficacy, and biocompatibility